The Fluorine‐Rich Electrolyte as an Interface Modifier to Stabilize Lithium Metal Battery at Ultra‐Low Temperature. (4th March 2022) - Zhang, Da; Zhu, DaWei; Guo, WenYao; Deng, ChenWei; Xu, QunJie; Li, HeXing; Min, YuLin
Abstract: Lithium (Li) metal batteries (LMBs) are still limited by lithium dendrite growth and solvated structure at low temperatures. A stable solid electrolyte interface (SEI) and solvent sheath structure are the future directions of liquid metal battery development. However, most artificial SEIs and electrolytes cannot meet the original objective of high conductivity and low nucleation potential multifunctional design. To address this challenge, an electrolyte with excellent high current density and low‐temperature performance is reported here. In this electrolyte environment, the thickness and microstructure of the "Chain Link Ships" SEI are formed. Moreover, the additives improve the desolvation ability of Li + in the ester electrolytes. Under the harsh environment (−30 °C), the average coulombic efficiency (CE) of the Li||copper (Cu) battery reaches 98% after 200 cycles. Even at −40 °C, the Li||LiFePO4 (LFP) battery shows 90% capacity retention after 100 cycles at the cathode‐limited areal capacity (5 mAh cm −2 ). Furthermore, at 30 °C, the Li||LFP battery can cycle stably for 1200 cycles at 5 C, and the capacity retention reaches 93.5%. This addition strategy provides insights into the commercial application of new solvated structure electrolytes and a new approach for commercial low‐temperature LMBs. Abstract : The modified electrolyte as an interface modifier to stabilize lithium metal anode and Lithium iron phosphate.